2008
DOI: 10.1111/j.1532-5415.2008.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Urinary Collection Devices in Skilled Nursing Facilities in Five States

Abstract: Coinciding with federal regulations, urinary catheterization was lower than has been reported previously and declined over time. Further reduction should be targeted at the evaluation of skin problems, appropriateness of multiple medications, and alternative measures in patients with diabetes mellitus, obesity, deep vein thrombosis, and communication problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…The enrollment period for the study was 36 months. Based on preliminary data, 911 we estimated that each NH would care for a mean of 22 residents with an indwelling device per year. Power calculations were based on anticipating a 30% reduction (rate ratio, 0.70) in MDRO prevalence as a result of our intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The enrollment period for the study was 36 months. Based on preliminary data, 911 we estimated that each NH would care for a mean of 22 residents with an indwelling device per year. Power calculations were based on anticipating a 30% reduction (rate ratio, 0.70) in MDRO prevalence as a result of our intervention.…”
Section: Methodsmentioning
confidence: 99%
“…5 While urinary catheter prevalence is lower in nursing homes than in the acute care setting, duration of use is often prolonged. 7, 10 In a setting where utilization is low, but use is prolonged, interventions designed to reduce UTI in acutely ill patients 11 may not be as helpful for preventing infection in nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…10,21 ' 22 While prior studies have also demonstrated regional variation in the use of urinary catheters after accounting for patient-level characteristics, these studies have been limited to claims data from older surgical populations 23 " 25 and patients residing in longterm care facilities. 26 Starting in August 2011, the Health Research and Educational Trust of the American Hospital Association and its academic partners have led On the CUSP: Stop CAUTI, an Agency for Healthcare Research and Quality-funded national initiative to reduce CAUTI in acute care hospitals. The organizational structure and key components of this national initiative have been described previously.…”
mentioning
confidence: 99%